Contributions to the 2014 and 2015 flight pattern and damages of Carpomyia schineri Loew. - Voigt, Erzsébet; Kelemen, Dóra; Tóth, Miklós (Acta Agraria Debreceniensis, 2015)
The fly Carpomyia schineri Loew is a pest of the berries of the feral Rosa canina group but is can also be found in the berries of grown rose cultivars. The larva damages the flesh of the berry, several larvae can develop inside a single berry. It can decrease the quantity and ascorbic acid content of the tea and jam, which are important human ascorbic acid sources during winter. At the same time in trapping experiments the adult can be confounded with adults of the walnut husk fly (Rhagoletis completa Cresson). In collections of berries at several sites in Hungary damage levels ranged from 0.88% to 65.08 %. Based on these damage levels we had the impression that the yellow sticky traps CSALOMON® PALz or PALs baited with the synthetic Rhagoletis lure caught moderate numbers of adults and were not satisfactory for detection, consequently improving trapping methods is necessary in the future.